2007
DOI: 10.1242/jcs.03333
|View full text |Cite
|
Sign up to set email alerts
|

Ena/VASP proteins mediate repulsion from ephrin ligands

Abstract: Ena/VASP proteins negatively regulate cell motility and contribute to repulsion from several guidance cues; however, there is currently no evidence for a role downstream of Eph receptors. Eph receptors mediate repulsion from ephrins at sites of intercellular contact during several developmental migrations. For example, the expression of ephrin-Bs in posterior halves of somites restricts neural crest cell migration to the anterior halves. Here we show that ephrin-B2 destabilises neural crest cell lamellipodia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 57 publications
4
17
1
Order By: Relevance
“…Our finding that VAB-1 negatively regulates UNC-34/Ena is different from a previous report that shows mammalian EphB4 as an activator of Ena/VASP [24]. In fibroblast cells, the EphB4 receptor is thought to activate Ena/VASP to destabilize lamellipodia during cell repulsion and likely does so by promoting elongated actin filaments rather than a branched actin filament network.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding that VAB-1 negatively regulates UNC-34/Ena is different from a previous report that shows mammalian EphB4 as an activator of Ena/VASP [24]. In fibroblast cells, the EphB4 receptor is thought to activate Ena/VASP to destabilize lamellipodia during cell repulsion and likely does so by promoting elongated actin filaments rather than a branched actin filament network.…”
Section: Discussioncontrasting
confidence: 99%
“…A previous report indicated that Ena/VASP was required for repulsion caused by EphB4 signaling in fibroblasts, but it was unclear how the signal was conveyed [24]. The Ena/VASP family are composed of an N-terminal EVH1 domain, a central PRO region and a C-terminal Ena/VASP homology II domain (EVH2) [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 K). Only when we applied MsEph-Fc at the onset of migration did we observe a global effect on EP cell motility, akin to the phenomenon of growth cone collapse in vitro (Harbott and Nobes, 2005;Evans et al, 2007). One explanation for this difference is that within the developing ENS, the EP cells may be most sensitive to MsEphrin-dependent signaling during their initial stages of migration, when each neuron extends a wide array of exploratory filopodia before aligning with a particular band pathway (Copenhaver et al, 1996;Wright et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…During targeting, growth cones at axon tips provide a dynamic platform for integration of attractive and repulsive guidance cues (Lowery and Van Vactor, 2009). Through binding to membrane receptors displayed on growth cones, guidance cues orchestrate dynamic changes of the cytoskeleton, in particular of the actin and microtubule networks (Driessens et al, 2001;GordonWeeks, 2004;Kalil and Dent, 2005;Evans et al, 2007;Lowery and Van Vactor, 2009). The growth cone consists of actin-rich structures, finger-like filopodia, and veil-like lamellipodia.…”
Section: Introductionmentioning
confidence: 99%